ANALYSIS OF THE INFLUENCE OF EXCHANGE RATES, INTEREST RATES AND INFLATION ON STOCK PRICE INDICES (CASE STUDY ON TRANSPORTATION COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE) - Dede Pramurza (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This research aims to analyze the influence of exchange rates, interest rates and inflation on the stock price index of transportation companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using the multiple linear regression method, this research examines the relationship between these macroeconomic variables and fluctuations. stock price. The results of the analysis show that although the model has a high coefficient of determination (R² = 95%), the influence of each variable is not always statistically significant. Exchange rates and interest rates tend to have a negative relationship with stock prices, while inflation shows varying impacts depending on economic conditions. These findings reflect the importance of macroeconomic stability in supporting capital market performance and providing insight for investors and policy makers in making investment decisions. This research also highlights the need for further studies to understand the dynamics of the relationship between these variables in the context of the transportation sector in Indonesia